Incidence of endocrine-related immune-related adverse events in Japanese subjects with various types of cancer - Iwamoto, Yuichiro; Kimura, Tomohiko; Iwamoto, Hideyuki; Sanada, Junpei; Fushimi, Yoshiro; Katakura, Yukino; Tatsumi, Fuminori; Shimoda, Masashi; Nakanishi, Shuhei; Mune, Tomoatsu; Kaku, Kohei; Kaneto, Hideaki (Frontiers in Endocrinology, 2023)
Background. Immune checkpoint inhibitors (ICIs), such as cytotoxic T lymphocyte antigen-4 (CTLA-4) inhibitors, programmed cell death protein 1 (PD-1) inhibitors, and programmed cell death protein 1 ligand 1 (PD-L1) inhibitors, are often used to treat a variety of malignancies. ICIs are known to cause endocrine-related immune-related adverse events (irAEs), but the incidence varies among reports and/or agents. This study evaluated the incidence of endocrine-related irAEs in patients who were treated with ICIs in Japan. Method. This single-center, retrospective, observational study examined the incidence and clinical characteristics of endocrine-related irAEs in 466 participants who were treated with ICIs at Kawasaki Medical School Hospital. Result. The mean age of participants with and without endocrine-related irAEs was 69.1 ± 1.8 years and 68.1 ± 1.1 years, respectively, with no difference between them. The overall incidence of any endocrine-related irAEs among the participants was 25.5%. Hypothyroidism was prevalent in 24.3%, hypoadrenocorticism in 3.2%, hypopituitarism in 0.9%, and insulin-dependent diabetes mellitus in 1.1%. Participants receiving combination therapy with CTLA-4 and PD-1 inhibitors had a significantly higher incidence of endocrine-related irAEs than those receiving monotherapy. Conclusion. Endocrine-related irAEs correlated significantly with survival and mean observation period. There was substantial difference in the incidence of endocrine-related irAEs among various types of ICIs and types of cancer. We should bear in mind that endocrine testing is necessary during the treatment with ICIs.